Clinical significance of elongation factor-1 delta mRNA expression in oesophageal carcinoma - Ogawa, K (Nature Publishing Group, 2004)
Elongation factor-1 (EF-1) delta is a subunit of EF-1, which is a protein complex that participates in the elongation step of mRNA translation and has recently been considered to correlate with oncogenic transformation. However, there has been no information regarding the clinical significance of EF-1 delta mRNA expression in malignant tumours, including oesophageal carcinoma. Thus, we quantitated the expression of EF-1 delta in malignant and benign oesophageal tissues and associated these levels with clinicopathologic parameters of oesophageal carcinoma. Paired oesophageal tissue samples from cancerous and corresponding noncancerous parts were obtained from 52 patients who underwent curative oesophagectomy. Quantitative analyses of EF-1 delta expression were performed using real-time quantitative reverse transcription–polymerase chain reaction. Elongation factor-1 delta mRNA overexpression in cancerous tissues compared to normal counterparts was observed in 38 of 52 (73%) patients. The mean expression level of EF-1 delta mRNA in cancerous tissues was significantly higher than that in noncancerous tissues (P<0.01). A higher expression of EF-1 delta was significantly correlated with lymph node metastases (P<0.05) and advanced stages (P<0.05). Furthermore, the cause-specific survival of patients with a higher expression of EF-1 delta was significantly poorer than those with a lower expression (5-year cause-specific survival rates; 23 and 54%, respectively, P<0.05). The results of this study indicated that EF-1 delta mRNA expression was significantly higher in cancerous compared to noncancerous oesophageal tissues, and a higher expression of EF-1 delta mRNA was correlated with lymph node metastases, advanced disease stages and poorer prognosis for patients with oesophageal carcinoma.